Interplay between interfacial energy, contact mechanics, and capillary forces in EGaIn droplets - Amini, Shahrouz (2022)
Eutectic gallium-indium (EGaIn) is increasingly employed as an interfacial conductor material in molecular electronics and wearable healthcare devices owing to its ability to be shaped at room temperature, conductivity, and mechanical stability. Despite this emerging usage, the mechanical and physical mechanisms governing EGaIn interactions with surrounding objects─mainly regulated by surface tension and interfacial adhesion─remain poorly understood. Here, using depth-sensing nanoindentation (DSN) on pristine EGaIn/GaOx surfaces, we uncover how changes in EGaIn/substrate interfacial energies regulate the adhesive and contact mechanic behaviors, notably the evolution of EGaIn capillary bridges with distinct capillary geometries and pressures. Varying the interfacial energy by subjecting EGaIn to different chemical environments and by functionalizing the tip with chemically distinct self-assembled monolayers (SAMs), we show that the adhesion forces between EGaIn and the solid substrate can be increased by up to 2 orders of magnitude, resulting in about a 60-fold increase in the elongation of capillary bridges. Our data reveal that by deploying molecular junctions with SAMs of different terminal groups, the trends of charge transport rates, the resistance of monolayers, and the contact interactions between EGaIn and monolayers from electrical characterizations are governed by the interfacial energies as well. This study provides a key understanding into the role of interfacial energy on geometrical characteristics of EGaIn capillary bridges, offering insights toward the fabrication of EGaIn junctions in a controlled fashion.